Perceptions of 10th Grade EFL Students on Using Spotify as Part of Classroom Activities in Developing Vocabulary through Listening to English Songs - Aristia, Diandra Putri; Rahmah, Leny Saili; Gaffar, Muhammad Andriana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the perceptions of 10th-grade EFL students on using Spotify as a tool to improve vocabulary through listening to English songs. The study highlights Indonesian high school students' challenges in mastering vocabulary and evaluates the potential of digital platforms such as Spotify in supporting the language learning process. This study uses a quantitative descriptive survey approach, 60 students from SMAN 25 Bandung participated in a five-point Likert scale questionnaire to assess their perceptions of Spotify’s usefulness, ease of access, educational benefits, and obstacles encountered. The results showed that students positively rated Spotify as an effective, enjoyable, and accessible vocabulary learning tool. Most participants agreed that listening to English songs helped them remember new vocabulary, improve pronunciation, and broaden their understanding of formal and informal expressions. The descriptive statistical analysis showed that four out of five leading indicators were categorized as “High” and one indicator was “Very High” regarding perceived benefits. However, there were several obstacles, such as difficulty understanding fast-paced lyrics, slang in lyrics, informal language use, and background music distractions. Despite these obstacles, students were highly motivated and preferred song-based learning methods over traditional, conventional, textbook-based ones. These findings emphasize Spotify’s potential as an effective vocabulary learning medium that aligns with the digital preferences of today’s generation and support the argument for integrating technology in EFL.